Mechanism of hydraulic fracture propagation and fracturing process optimization in thin-interbedded sandstone-shale reservoirs based on 3D discrete lattice method - Sun, Dongzheng; Xu, Fabin; Ma, Lei; Li, Long; Han, Cheng (Frontiers in Earth Science, 2025)
In this study, a mechanical model of reservoir and interlayer structure is constructed based on three-dimensional discrete lattice method, and the fracture propagation rule and control factors of hydraulic fracturing in sand-mudstone thin interlayer reservoir are systematically discussed. The results show that: 1) the ratio of elastic modulus of the reservoir significantly affects the vertical propagation of fractures. When the ratio is <0.5, the fracture propagation is suppressed, while when the ratio is >1, the fracture propagation is promoted; 2) The minimum horizontal ground stress difference between layers is more than 7 MPa, which can effectively inhibit the propagation of cracks through layers; 3) The combination of a high-viscosity fracturing fluid (≥40 mPa·s) and a high injection rate (≥8 m3/min) enhances fracture penetration, while the “high-low viscosity” combined injection strategy collaboratively optimizes primary fracture expansion and weak interzonal surface opening. Therefore, the process optimization scheme is proposed: 60 mPa·s high viscous surface is used when the barrier modulus is <6,000 MPa, 10 mPa·s low viscous activated weak surface is selected when the reservoir-interlayer stress difference is <5 MPa, multi-stage proppant combination and 8–10 m3/min injection displacement control are used to achieve the optimal configuration of technical and economic parameters. This study provides theoretical basis and engineering guidance for fracturing reconstruction of thin interlayer reservoir.